PENGARUH SCARCITY TERHADAP IMPULSE BUYING PADA PRODUK FASHION DALAM LIVE STREAMING TIKTOK MELALUI AROUSAL SEBAGAI VARIABEL INTERVENING - Erna Diana Yanti; Netti Nurlenawati; Dexi Triadinda (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to explore the impact of implementing scarcity strategies on impulse buying behavior on TikTok live streaming, with the role of arousal as a mediating variable. The research method used is a quantitative approach with a survey design, which collects data from 97 TikTok users who actively purchase fashion products through live streaming. The data analysis techniques applied include path test and Sobel test to test the role of mediation. The research findings revealed that scarcity strategies exert a significant influence on emotional arousal and impulse buying, both directly and through the mediating role of arousal. Time and quantity scarcity strategies increase consumers' emotional arousal, which further drives impulse buying behavior. This study provides practical implications for marketers to effectively utilize scarcity strategies to increase consumer purchase decisions during live streaming, while providing insight into the role of arousal in the decision-making process. Future research is recommended to include additional variables, such as consumer trust or perceived value, to broaden the understanding of the factors that influence impulse purchases on other e-commerce platforms.